2014
DOI: 10.1242/jeb.111245
|View full text |Cite
|
Sign up to set email alerts
|

Milk output and composition in mice divergently selected for BMR

Abstract: From an evolutionary perspective, the high basal metabolic rate (BMR) of homeotherms is hypothesised to be a by-product of natural selection for effective parental care. We estimated daily milk output during two consecutive lactation bouts in mice divergently selected for high/low BMR and applied a cross-fostered design to control for potential differences in the between-line suckling abilities of nursed juveniles. Additionally, to remedy the potential limitation imposed by the ability of mother mice to dissip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In previous studies we found that a significant difference in parental effort between the two line types is most prominent when selected mice are lactating at an ambient temperature of 17°C, i.e., significantly lower than the housing temperature of 23°C. This difference was manifested both in higher pup growth rate (Sadowska et al, 2013) and higher milk production in the H-BMR mice (Sadowska et al, 2015a). Since higher rates of BMR are associated with high heat production, it is tempting to attribute higher reproductive output of the H-BMR type mice at low ambient temperatures to a release from the heat constraint.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies we found that a significant difference in parental effort between the two line types is most prominent when selected mice are lactating at an ambient temperature of 17°C, i.e., significantly lower than the housing temperature of 23°C. This difference was manifested both in higher pup growth rate (Sadowska et al, 2013) and higher milk production in the H-BMR mice (Sadowska et al, 2015a). Since higher rates of BMR are associated with high heat production, it is tempting to attribute higher reproductive output of the H-BMR type mice at low ambient temperatures to a release from the heat constraint.…”
Section: Discussionmentioning
confidence: 99%
“…with an intrinsically high basal metabolic rate (H-BMR). In our previous work on a unique model, mice from two line types, one selected for H-BMR and the other for low basal metabolic rate (L-BMR), we were able to demonstrate a significant positive correlation between parental effort (quantified as pup growth rate and milk output; Sadowska et al, 2013) with BMR (Sadowska et al, 2015a). The differences between the two line types were, however, most prominent when animals at peak lactation were exposed to a temperature lower than that of normal housing conditions (17°C versus 23°C).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations